The differences of nutrition status, energy delivery and outcomes between metropolis and regional university-based thai surgical intensive care units - Kaweesak Chittawatanarat (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: The objective of this study was to compare the differences of nutrition status, nutrition delivery, and the outcomes between the metropolis (MUH) and regional university based hospitals (RUH) in Thailand. Material and Method: The nutrition data were retrieved from the THAI-SICU database. A total of 1,686 patients (MUH 927 patients vs. RUH 759 patients) with completion of nutrition status and nutrition delivery data were included in this analysis. The enrolled patients from study centers located in Bangkok were defined as MUH, and the patients from Chiang Mai were defined as RUH. Patient characteristics, nutrition status using the subjective global assessment (SGA) and nutrition risk screening (NRS), nutrition delivery, and outcomes of treatment were recorded. The outcome associations were analyzed by a multivariable regression model. Results: At admission, there were significant differences of age, gender, body mass index, disease severity, albumin level, and diagnosis. RUH had significantly poorer nutritional status than MUH (RUH vs. MUH: SGA class B and C, 57.7% vs. 37.1%, p<0.001; NRS at risk, 56.3% vs. 38.4%, p<0.001). The tendency of total calories and enteral nutrition delivery per day of RUH was significantly lower than MUH especially in the first three weeks of hospitalization. Carbohydrates were the main resource for parenteral nutrition. Although there was no difference of protein delivery, MUH had a significantly higher prescription of fat emulsion especially in the 1st-2nd weeks. Even though there were higher occurrences of intensive care unit (ICU) mortality, 28-day mortality, sepsis occurrence, ICU length of stay (LOS), and hospital LOS in RUH, the multivariable analysis did not demonstrate the statistical value of these outcomes. Conclusion: RUH had a poorer nutritional status. MUH had more total caloric intake and enteral nutrition delivery per day especially during the first three weeks. However, the treatment outcomes showed no differences in multivariable analysis.